Why poison your baby? - Abd Razak, Dzulkifli (1995)
IN 1961, A GERMAN NEWSPAPER drew the attention of the public to the harmful effects of a newly introduced sleeping pill thalidomide used during pregnancy. It warned of the possiblity of foetal deformities, especially phocomelia, or more popular known as "flipperbabies". Phocomelia is a very rare type of inborn malformation, but following the use of thalidomide, about 10,000 cases were found in many countries, particularly in Europe. Thalidomide was later classified as a teratogen and was eventually banned. But it was too late. Its traumatic effects extended far beyond the victims' families. It was a bitter lesson for society at large.